Phoenix math for the 21st century learners 8 - Gloria, Jonathan C.; Guadayo, Joseph L.; Lelina, Robert G.; Tan, Josephine lorenzo S.; Degolacion, Roberto J.; Chua, Simon L. (Quezon City. Phoenix Publishing House, Inc., 2017)
"This textbook aims to help students learn to think mathematically and to help them see how mathematics works in a moderm society. each section is usually introduced through the use of inductive or deductive reasoning; that is, students are provided with several examples so that they ca make propositions out of the illustrations given. Based on their mathematical experiences, students are given opportunities to cite as many examples or counterexamples as possible whenever concepts are presented using abstract mathematical ideas".
English text.
Keywords: Mathematics -- Study and Teaching